2009
DOI: 10.1002/jssc.200900233
|View full text |Cite
|
Sign up to set email alerts
|

Immuno‐capture as ultimate sample cleanup in LC‐MS/MS determination of the early stage biomarker ProGRP

Abstract: This paper presents a selective and efficient sample preparation procedure for NLLGLIEAK, signature peptide for the small cell lung cancer (SCLC) biomarker ProGRP, in human serum. The procedure is based on immuno-capture of ProGRP in 96-wells microtiter plates coated with the mAb E146. After immuno-capture and thorough rinse, trypsin was added for in-well digestion. Subsequently the signature peptide was enriched by SPE and determined by LC-MS/MS. Various steps in the procedure were optimized to achieve a low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…Oxidation levels of blood proteins may reveal physiological conditions (Aldini et al, 2006(Aldini et al, , 2008Morgan et al, 2007;Bruschi et al, 2008) and might be detected by biotin hydrazide to selectively derivatize carbonyl groups in oxidized proteins followed by avidin affinity chromatography (Mirzaei et al, 2008). Protein adducts may form in response to physiological processes (Szapacs et al, 2006(Szapacs et al, , 2008 or may be indicative of the presence of specific mutagens, toxins, drug binding, or chemical weapons (Yike et al, 2006;Carol-Visser et al, 2008;Lohmann, Hayen, & Karst, 2008;Myers & Ali, 2008;Scholl & Groopman, 2008;Smith et al, 2008;Noort et al, 2008a,b;Will, Wolters, & Sheldrick, 2008;Zhang et al, 2008a;Moreno-Gordaliza et al, 2009;Preston et al, 2009;Winther et al, 2009). Protein serotonylation may have a physiological function since transglutaminase activity was observed as a cystamine-inhibitable incorporation of the free amine pentylamine-biotin into arterial proteins integral to contractility and the cytoskeleton (Schaub et al, 2009).…”
Section: K Post-translational Modificationmentioning
confidence: 96%
See 2 more Smart Citations
“…Oxidation levels of blood proteins may reveal physiological conditions (Aldini et al, 2006(Aldini et al, , 2008Morgan et al, 2007;Bruschi et al, 2008) and might be detected by biotin hydrazide to selectively derivatize carbonyl groups in oxidized proteins followed by avidin affinity chromatography (Mirzaei et al, 2008). Protein adducts may form in response to physiological processes (Szapacs et al, 2006(Szapacs et al, , 2008 or may be indicative of the presence of specific mutagens, toxins, drug binding, or chemical weapons (Yike et al, 2006;Carol-Visser et al, 2008;Lohmann, Hayen, & Karst, 2008;Myers & Ali, 2008;Scholl & Groopman, 2008;Smith et al, 2008;Noort et al, 2008a,b;Will, Wolters, & Sheldrick, 2008;Zhang et al, 2008a;Moreno-Gordaliza et al, 2009;Preston et al, 2009;Winther et al, 2009). Protein serotonylation may have a physiological function since transglutaminase activity was observed as a cystamine-inhibitable incorporation of the free amine pentylamine-biotin into arterial proteins integral to contractility and the cytoskeleton (Schaub et al, 2009).…”
Section: K Post-translational Modificationmentioning
confidence: 96%
“…The dilution of synthetic, multi-plexed or isotopic-or isobaric-labeled peptides as internal or external standards series may provide absolute quantification (Gerber et al, 2003;Beynon et al, 2005;Bondar et al, 2007;Berna et al, 2008;Haqqani, Kelly, & Stanimirovic, 2008b). Targeted LC-ESI-MS/MS analysis, with external or internal standards, is a well-established and absolute quantification might be obtained with triple quadrupole or many other mass spectrometers (Anderson & Hunter, 2006;Immler, Greven, & Reinemer, 2006;Melanson, Chisholm, & Pinto, 2006;Lin, Shaler, & Becker, 2006a;Bondar et al, 2007;Kay et al, 2007;Keshishian et al, 2007;Xia, Wu, & Jemal, 2008;Pan et al, 2008b;Anderson et al, 2009;Winther et al, 2009). Relatively low abundance analytes in the 1 ng/mL range can be directly detected by partition chromatography followed by LC-MS analysis (Hoofnagle et al, 2008;Fortin et al, 2009;Tucholska et al, 2009).…”
Section: Targeted and Internally Or Externally Standardized Mass Specmentioning
confidence: 99%
See 1 more Smart Citation
“…Combing the selectivity of an immunoaffinity capture with the selectivity of a LC-MS/MS system can allow a 1000-fold enrichment in comparison to conventional techniques [24]. Although this technique requires specialized antibodies, it provides sufficient purification to achieve quantification of low abundance proteins from plasma [24,[28][29][30][31]. Low recoveries and cross reactivities are some of the issues seen during immunocapture enrichment [32,33].…”
Section: Immunoaffinity Enrichmentmentioning
confidence: 99%
“…Winther et al reported an LC-MS/MS method for quantification of progastrin-releasing peptide (ProGRP), a small cell lung cancer biomarker, in human serum using an acetylated form of the protein as an internal standard [30]. The IS was made in-house by specific acetylation of the lysine side chains in ProGRP (31-98) by using N-hydroxysuccinimide-based ester acetic acid N-hydroxysuccinimide (AA-NHS) as the acetylating reactant.…”
Section: Derivatized Protein Internal Standardmentioning
confidence: 99%